Mediational Effect of Fairburn’s Transdiagnostic Mechanisms Between Attachment to the Mother and Eating Disorder Symptoms in a Clinical Sample - Cortés-García, Laura; Martínez Calvo, Carmen; Senra, Carmen (Frontiers in Psychology, 2022)
Objective: Research has supported a link between insecure attachment and eating disorders (EDs); however, little is known about how this influence is exerted in young female EDs patients. This study tested, for the first time, a multiple mediational model, wherein the four Fairburn’s transdiagnostic mechanisms mediated the relationship between attachment to the mother and ED symptoms. Method: A total of 101 female young EDs patient aged 15–24 were administered the Inventory of Parent and Peer Attachment, Eating Disorder Inventory-3 and Eating Attitudes Test-26 to assess attachment, the four transdiagnostic maintaining mechanisms and ED symptoms, respectively. Results: Comparison analyses showed that there were no significant differences between the diagnostic groups in terms of attachment and the transdiagnostic variables. Multiple mediational analyses indicated that low self-esteem and clinical perfectionism were significant mediators between insecure attachment to the mother and ED symptoms, while controlling for depressive symptoms. Conclusions: These findings suggest that the distal risk influence of insecure attachment to the mother in the development of ED symptoms might be explained by low self-esteem and high clinical perfectionism, controlling for depressive symptoms. Further investigation into the efficacy of cognitive-behavioral treatments targeting insecure attachment representations for young EDs patients is recommended.